2013
DOI: 10.7567/jjap.53.012301
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of Cu(In,Ga)Se2 solar cell performance toward 23% conversion efficiency

Abstract: The effects of conduction band grading in a Cu(In,Ga)Se2 (CIGS) thin film with an average bandgap of 1.4 eV on solar cell performance were investigated by changing the minimum bandgap (E gmin) and its position, employing the software wxAMPS. The calculation was carried out, taking CdS/CIGS heterointerface recombination into account, by incorporating a thin defective layer into the interface. For CIGS with a flat conduction band profile, i.e., without conduction band grading, the effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 24 publications
1
43
0
1
Order By: Relevance
“…The conduction band profile of typical CIGS solar cells fabricated by the three stage method has double graded (DG) structure which is useful for the improvement of carrier collection efficiency by an internal electric field, and the improvement of open circuit voltage ( V OC ) by bandgap‐widening in a depletion region. On the other hand, single graded (SG) structure has been reported lower V OC than DG structure due to no bandgap‐widening in a depletion region . However, in this study from experimental results we found that SG structure has higher efficiency than DG structure.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…The conduction band profile of typical CIGS solar cells fabricated by the three stage method has double graded (DG) structure which is useful for the improvement of carrier collection efficiency by an internal electric field, and the improvement of open circuit voltage ( V OC ) by bandgap‐widening in a depletion region. On the other hand, single graded (SG) structure has been reported lower V OC than DG structure due to no bandgap‐widening in a depletion region . However, in this study from experimental results we found that SG structure has higher efficiency than DG structure.…”
Section: Introductionmentioning
confidence: 53%
“…To apply the SG structure to CIGS solar cells with high Ga contents, we fabricated SG‐CIGS solar cells with E g = 1.2 eV at the surface side and E g = 1.6 eV at the back side ( E g(avg) = 1.4 eV) which was structure optimized by Hirai et al and investigated the influence of the OVC layer on solar cell performance by compared to DG‐CIGS with E g(avg) = 1.4 eV. Figures and show J – V characteristics, external quantum efficiency (EQE) and GGI depth profile, respectively, in DG‐ and SG‐CIGS solar cells with E g(avg) = 1.4 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it could be confirmed that the high η of about 18% was also obtained by insertion of a thinner Cu(In,Ga) 3 Se 5 layer like a few nanometers even though the layer had high N AG of 10 18 cm -3 . So far in our group, it has been revealed that the open circuit voltage is improved due to suppression of interfacial recombination by repelling holes at the ∆E V if wide gap layer with ∆E V is inserted [11,12]. From these calculation results, it was shown that the ∆E V control at CdS/CIGS and GBs is very important for realization of high-efficiency CIGS solar cells and that the insertion of thin Cu(In,Ga) 3 Se 5 layer is a promising technique even though the layer has high defect density.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Cu(In,Ga) 3 Se 5 is one of the materials which has lower Cu contents more than CIGS and has valence band offset (ΔE V ) of about 0.3 eV [8,10]. Our group has revealed that suppression effect of interfacial recombination is obtained due to repelling holes by the ΔE V , if a wide gap layer with the ΔE V is inserted at the CdS/CIGS interface for CIGS solar cell [11,12]. In this study we disclosed a correlation between formation of a Cu-poor layer and solar cell characteristics, and comprehensively investigated influence by variation of Cu component in surface, GB and grain interior (GI) of CIGS thin films by theoretical and experimental.…”
Section: Introductionmentioning
confidence: 99%
“…Успехи фотовольтаического преобразования энергии излучения с помощью тонкопленочных солнечных эле-ментов связаны с фотопреобразователями на основе пле-нок CdTe (эффективность ∼ 21%) и CuInGaSe (CIGSe) (> 20%) [1][2][3]. Содержание в данных материалах ток-сического Cd, редких и дорогих металлов In и Ga существенно препятствует их широкому коммерческому использованию.…”
Section: Introductionunclassified